2010
DOI: 10.2478/v10003-010-0024-2
|View full text |Cite
|
Sign up to set email alerts
|

The Grain Size Influence on the E1' Centre Observed in Quartz of Atmospheric Deposition at Two Japanese Cities: A Preliminary Study

Abstract: Abstract:The grain size influence on the number of oxygen vacancies in quartz was investigated by ESR in atmospheric deposition collected at two Japanese cities, Fukuoka and Akita, in 1969 and 1971. The finer grain size fraction shows the highest value of concentration of oxygen vacancies, most closely resembling dust originating in the Taklamakan desert. Month to month and year to year variation of the dependence was also observed which could possibly be attributed to the variation of the mixture ratio of at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This study aims to utilize the potential of electron spin resonance (ESR) dating technique, as an alternative to U-series dating technique, on the speleothem collected from several caves in the AMR. ESR dating has been applied to a wide variety of materials including speleothems, teeth, and carbonate cements, especially in the context of paleoclimatology, paleoenvironment and archeology (Ulusoy and Ikeya, 2000;Whitehead et al, 2002;Ulusoy, 2004a,b;Schellmann et al, 2008;Yamamoto et al, 2010). Many authors have reported good agreement between U-series and ESR ages for speleothems (Rink, 1997;Skinner, 2000;Blackwell, 2006;Schellmann et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This study aims to utilize the potential of electron spin resonance (ESR) dating technique, as an alternative to U-series dating technique, on the speleothem collected from several caves in the AMR. ESR dating has been applied to a wide variety of materials including speleothems, teeth, and carbonate cements, especially in the context of paleoclimatology, paleoenvironment and archeology (Ulusoy and Ikeya, 2000;Whitehead et al, 2002;Ulusoy, 2004a,b;Schellmann et al, 2008;Yamamoto et al, 2010). Many authors have reported good agreement between U-series and ESR ages for speleothems (Rink, 1997;Skinner, 2000;Blackwell, 2006;Schellmann et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…(Nagashima et al, 2007b). Yamamoto et al (2010) investigated, the number of oxygen vacancies in quartz of atmospheric deposition to Japanese cities in recent past. They found that the number of oxygen vacancies in quartz is larger in finer fractions, where the highest values in those fractions are consistent with the value of the samples from Taklamakan desert.…”
Section: The Horizontal Axis For the Natural Quartz (Closed Circlesmentioning
confidence: 99%